1976
DOI: 10.1177/140349487600400108
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Problems in Patients Suffering from Multiple Sclerosis

Abstract: A questionnaire which allowed anonymous answering and which also included many other questions besides those dealing with sexual life was sent to 302 patients suffering from multiple sclerosis (MS). Sexual life had changed for 91% of males and 72% of females. About half of the patients replied that their sexual life was unsatisfactory or had ceased altogether. These patients were as a rule in a relative poor physical condition. In males, disturbances in erection (62%) were the most common problem, erection was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 1 publication
2
13
1
Order By: Relevance
“…Research has shown that as many as 72% of women with MS have sexual dysfunction [32]. Moreover, complaints may be related to physiologic and psychologic issues.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Research has shown that as many as 72% of women with MS have sexual dysfunction [32]. Moreover, complaints may be related to physiologic and psychologic issues.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Many studies have shown a high prevalence of sexual dysfunction in MS patients [5][6][7][11][12][13][14][15][16][17][18][19][20][21]. A study by McCabe showed that patients with MS had lower levels of sexual activity and sexual satisfaction compared with healthy controls [18].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in the identification of factors associated with the HRQoL of MS patients [1][2][3][4]. Bladder, bowel and sexual dysfunction are common symptoms of MS [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. They can occur at any time during the course of MS. Several studies have shown that they can be the source of significant disability and result in a reduction of HRQoL [5][6][7][8][9][10][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][34][35][36][37] Spinal cord injury may affect sexual function and, although controversial, women with spinal cord lesions at T1 and below are probably anorgasmic. 1,29,36 In addition, women who have neurologic diseases such as Parkinson's disease or multiple sclerosis may have sexual problems.…”
Section: Historymentioning
confidence: 99%
“…24,25 Despite the prevalence of FSD, many women may be too embarrassed or reluctant to initiate a discussion of their sexual problems. [1][2][3][4] Unassuming questions such as, for instance "Are you sexually active?" followed by "Do you have any questions or concerns regarding your sexual health?"…”
Section: Evaluation Of Female Sexual Dysfunctionmentioning
confidence: 99%